A scoping review of oral health outcomes for people with cerebral palsy. (27th October 2021) - Lansdown, Karen; Irving, Michelle; Mathieu Coulton, Kimberly; Smithers‐Sheedy, Hayley
Abstract: Introduction: Good oral health is important for good overall health. Studies have reported poorer oral health outcomes for people with cerebral palsy, but there has been no synthesis of the evidence surrounding this and, there are no clear oral health recommendations for people with cerebral palsy globally. This review synthesizes the existing knowledge base on oral health in people with cerebral palsy and provides recommendations for future research. Methods: A scoping review was conducted to assess the current literature. Databases were searched using relevant search terms. Study outcomes were synthesized according to their reported outcomes. Results: One hundred seventy three studies were included in this review. Children with cerebral palsy have an increased risk for dental caries and untreated caries. Higher saliva osmolality is a major contributor to increased dental caries. People with cerebral palsy are more likely to experience tooth wear and bruxism. Children and their care‐givers have poor oral health related quality of life. There is a large unmet need for oral healthcare in this group. There is no suggested plan for the prevention of poor oral health for this group. A high number of studies included related to research is conducted in low‐ and middle‐income countries, care should be taken in applying results outside this context. There is a lack of research conducted in people with cerebral palsy, 18 years and over. Conclusion: There is a higher risk for poor oral health in people with cerebral palsy and there is a large unmet need to dental care in this group. This study highlights the need for further research to focus on adults with cerebral palsy and an of understanding the oral health care outcomes in the context of settings. The authors recommend the inclusion of classification systems and the integration of disability inclusive language in future studies.